Patients’ response during the co-circulation of multiple respiratory diseases in China—based on the self-regulation common-sense model - Sun, Shanwen; Wang, Yali; Hou, Hailong; Niu, Yuqi; Shao, Yefan; Chen, Linlin; Zhang, Xiaochun (Frontiers in Public Health, 2024)
BACKGROUND: Following the COVID-19 pandemic, another large-scale respiratory epidemic has emerged in China, causing significant social impact and disruption. The article is to explore the patients' psychological and behavioral responses to the enhancement of healthcare quality.Based on the five dimensions of the Self-Regulation Common-Sense Model, we developed an interview outline to explore the process by which patients identify disease symptoms to guide action plans and coping strategies. The researchers used a semi-structured interview format to simultaneously collect data online and offline. This study gathered data from 12 patients with mixed respiratory infections, comprising 58% females and 42% males; the average age was 30.67 years (SD 20.00), with 91.7% infected with two pathogens and 8.3% with three. The data analysis employed the KJ method, themes were inductively analyzed and categorized from semi-structured interview results, which were then organized into a coherent 2 visual and logical pathway. KEY RESULTS: The study identified 5 themes: (1) Autonomous Actions Prior to Seeking Medical Care; (2) Decision-Making in Seeking Hospital Care; (3) Disease Shock; (4) Public Crisis Response; (5) Information Cocoon. CONCLUSIONS: The pandemic of respiratory infectious diseases has not ceased in recent years. Following the COVID-19 pandemic, China is now facing a trend of concurrent epidemics involving multiple respiratory pathogens. This study centers on patients' health behaviors, exploring the potential relationships among various factorsthat affect these behaviors. The aim is to provide references and grounds for the improvement of healthcare services when such public health events reoccur.